EKSTRAK KULIT BUAH NAGA MERAH (Hylocereus Polyrhizus) SEBAGAI ANTIOKSIDAN DALAM FORMULASI SEDIAAN LOTIO - Yuska Novi Yanty; Vetria Ade Siska (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2017)
Dragon fruit is a kind of cactus tree from the family Cactaceae. Red dragon fruit contains lots of vitamin C, vitamin E, vitamin B1, B2, and B3. These vitamins can increase energy, and metabolize food, and even improve skin quality. This study aims to determine whether red dragon fruit skin extract can be made into lotion preparation and to know the effect of variation of red dragon fruit skin extract on physical properties of lotio. Red dragon fruit skin was extracted by maceration, lotio was made using formulation with variation of dragon fruit skin extract which were F1 (3%), F2 (5%), F3 (7%). The lotio was making by mixing the oil phase into the water. Physical test results showed there was organoleptic change in F1, F2 and F3 after observation for 4 weeks. The average result of pH test for four weeks was meet the lotio requirements ranging from 4.5-8. F1 with an average of 6.5, F2 with an average of 7.25, F3 with an average of 7.5. The result of viscosity test is F1 0,5 poise, F2, F3 and F4 0 poise. The result of F1 7.0 cm, F2 7,1 cm and F3 7.5 cm. The irritation test results are not irritating on the use of F1, F2 and F3. The test results showed that F0 and F1 are more favorable. The result of this research was that red skin dragon fruit extract can be made into lotio formulation and there was influence of variation of extract concentration on the physical properties of lotio.